1990
DOI: 10.1086/168393
|View full text |Cite
|
Sign up to set email alerts
|

GINGA observations of quasi-periodic oscillations in type II bursts from the Rapid Burster

Abstract: GINGA observations of quasi-periodic oscillations in type II bursts from teh Rapid Burster Dotani, T.; Mitsuda, K.; Inoue, H.; Tanaka, Y.; Kawai, N.; Tawara, Y.; Makishima, K.; van Paradijs, J.; van der Klis, M.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 0 publications
1
32
0
Order By: Relevance
“…This may be related to the weak magnetic Ðeld. Presence of two accreting paths is also suspected in the other type II burster, the Rapid Burster, based on the observations of quasi-periodic oscillations (Dotani et al 1990). Two accretion paths may, therefore, be common to neutron stars that produce type II bursts.…”
Section: T He Pulsed Emissionmentioning
confidence: 99%
“…This may be related to the weak magnetic Ðeld. Presence of two accreting paths is also suspected in the other type II burster, the Rapid Burster, based on the observations of quasi-periodic oscillations (Dotani et al 1990). Two accretion paths may, therefore, be common to neutron stars that produce type II bursts.…”
Section: T He Pulsed Emissionmentioning
confidence: 99%
“…Quasi-periodic oscillations (QPO) in the range 12-7 Hz have been observed in the type II bursts and in the persistent emission between the bursts; their behavior is very complex (Tawara et al 1982; Stella et al 1988a, b;Dotani et al 1990;Lubin et al 1991;Rutledge et al 1995; LVT93; LVT95). Dotani et al (1990) showed that during the type II bursts the oscillations are due to a periodic modulation without phase jumps whose frequency changes by up to 125%.…”
Section: L39mentioning
confidence: 99%
“…Dotani et al (1990) showed that during the type II bursts the oscillations are due to a periodic modulation without phase jumps whose frequency changes by up to 125%. The frequency shifts can explain the width of the QPO peaks in the power density spectra.…”
Section: L39mentioning
confidence: 99%
See 1 more Smart Citation
“…Phenomena probably related to QPOs occur in (a) the black hole candidate system LMC X-1 [208], (b) the 1983 August 1 gamma ray burster [209], (c) the rapid burster [210], and (d) several massive …”
Section: Quasi-periodic Oscillations (Qpos)mentioning
confidence: 99%